Uso de recursos dinámicos en la enseñanza – aprendizaje de química para estudiantes de primero de bachillerato del centro de privación de Libertad Chimborazo N°1 - Chimbo Guzmán, Lilian Avigail (2023)
ABSTRACT: Based on the epistemology of the use of dynamic resources in the teaching-learning of Chemistry, applying to this research a proposal will be developed based on dynamic games as a strategy to improve the learning of first-year high school students at the center of deprivation of liberty CHIMBORAZO N°1. The effectiveness of the application of three dynamic games that were used to raise the theoretical and practical aspects is demonstrated. With the resolution of exercises and other activities they could be for staff who are confined and it was applied to the 18 high school students of the 2022-2023 school year with interviews and it is our study universe, there is no sample. This process strengthens the teaching-learning of the subject of Chemistry, which is quite a challenge since it seeks that students, through the use of dynamic resources (the game) and methodological strategies, can acquire skills that encourage reflective and critical thinking in the interpretation of the phenomena of the subject. The analysis of the data collected is carried out, and Tukey's methodology is applied, which analyzes confidence intervals for all the different groups between the means, while at the same time controlling the error rate. The Tukey test was applied to identify the relationship between the means of one event and another and demonstrate that there is a significant difference applying the three dynamic games that will be used as a pedagogical strategy. Keywords: Dynamic resources, methodological proposal, teaching, learning.